Odpowiedź :
Odpowiedź:
a)
3x + 2 + 7x = 5x - 5
3x + 7x - 5x = -5 -2
5x = -7
x = [tex]-\frac{7}{5}[/tex]
b)
[tex]1 - 6x - 3 - 2x = 4 + 4x + 11[/tex]
[tex]-6x -2x-4x=11+4+3-1[/tex]
[tex]-12x=17[/tex]
[tex]\blocked{x=-\frac{17}{12} }[/tex]
c)
[tex]8x - 9-2x+3=7x-4+3x[/tex]
[tex]8x-2x-7x-3x=-4-3+9[/tex]
[tex]-4x=2[/tex]
[tex]x=-0,5[/tex]
d)
[tex]\frac{5}{8} x+2=\frac{3}{8} x+4[/tex]
[tex]\frac{5}{8} x-\frac{3}{8} x=4-2[/tex]
[tex]\frac{2}{8} x=2[/tex]
[tex]x=8[/tex]
e)
[tex]\frac{5}{6} x+5=\frac{2}{3} x+3[/tex]
[tex]\frac{5}{6} x-\frac{4}{6} =3-5[/tex]
[tex]\frac{1}{6} x=-2[/tex]
[tex]x=-12[/tex]
Odpowiedź:
[tex]a)\\\\3x+2+7x=5x-5\\\\10x+2=5x-5\\\\10x-5x=-5-2\\\\5x=-7\ \ /:5\\\\x=-\frac{7}{5}\\\\x=-1\frac{2}{5}\\\\\\b)\\\\1-6x-3-2x=4+4x+11\\\\-2-8x=15+4x\\\\-8x-4x=15+2\\\\-12x=17\ \ /:(-12)\\\\x=-\frac{17}{12}\\\\x=-1\frac{5}{12}[/tex]
[tex]c)\\\\8x-9-2x+3=7x-4+3x\\\\6x-6=10x-4\\\\6x-10x=-4+6\\\\-4x=2\ \ /:(-4)\\\\x=-\frac{2}{4}\\\\x=-\frac{1}{2}\\\\\\d)\\\\\frac{5}{8}x+2=\frac{3}{8}x+4\ \ /\cdot8\\\\5x+16=3x+32\\\\5x-3x=32-16\\\\2x=16\ \ /:2\\\\x=8[/tex]
[tex]e)\\\\\frac{5}{6}x+5=\frac{2}{3}x+3\ \ /\cdot6\\\\5x+30=4x+18\\\\5x-4x=18-30\\\\x=-12[/tex]